Caminhar, (re)configurar e produzir curtas-Metragens: O relato de uma prática escolar em Ribeirão Preto/SP - De Mello, Rafael Cardoso [UNESP]; Lastoria, Andrea Coelho; De Almeida Santos, José Faustino (My University, 2015)
This article aims to analyze four short films developed by students of a private school in Ribeirao Preto, a city located in the state of São Paulo, in 2010. To support our interpretation, we initially conducted a theoretical discussion of the use cinema in the teaching of history and geography, as well as presenting some examples of groups of teachers and researchers who did the same thing in Brazil. With this in mind, we chose the contributions of Walter Benjamin and Paul Ricoeur, regarding a certain pedagogy of the cinematic look and the relationship between the audiovisual discourse and the reconfiguration of the real, respectively. From these bases and supported the desire for civic education, the authors of this article proposes a reading of short films produced by students, knowing that carry the world in their own way. Finally, we point out that we agree with the filmmaker Walter Salles when he says: the role of cinema is to generate a memory of ourselves..
Walk, reset and produce short films: The report of a school practice in Ribeirão Preto/SP
Keywords: History and geography teaching; Pedagogical practice; Short-films